A Juridical Perspective On Press Ethics in Reporting the Identity of Child Victims of Immorality: Between Public Interest and Children’s Rights - Joko Susanto; Ali Masyhar; Anis Widyawati (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2026)
Proper journalism in the reporting of child victims of immorality requires a strict ethical approach to protect the rights of victims and maintain the function of the press in conveying the truth. This article discusses important aspects such as victim protection, privacy rights, journalistic codes of ethics, and the role of the media in society. Through normative juridical analysis and descriptive research involving desk research and interviews with journalists, this article highlights the importance of striking a balance between freedom of speech and the social responsibility of the press. When covering sensitive issues like child sexual abuse, the press must uphold individual rights. We must adhere to the Journalistic Code of Ethics to ensure that the news does not violate the rights of victims. The role of the Press Council and law enforcement officials is crucial in enforcing the law, sanctioning violators, and ensuring justice for all parties. Analysis of the news indicates that there are still violations in the form of disclosing the identity of child victims, which should be kept confidential to protect their right to privacy and honor. This study confirms that safeguarding the honor and rights of victims, as well as supporting fair law enforcement and strict supervision of media practices, can create a responsible information environment. The findings provide an important reference for policymakers, media practitioners, and academics in improving the quality of ethical journalism that respects the rights of child victims of violence.